KEKERASAN DALAM RUMAH TANGGA DI DESA PALSA, KARTON PELALAWA (STUDI KASUS KEKERASAN TERHADAP ISTRI DI RUMAH) - Noni Kikies Sartiwi; Ashaluddin Jalil (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study aims to determine the causes of Domestic Violence. The research location was conducted in Palas Village, Pelalawan Regency. The method used is a qualitative method. The subjects in this study were 5 couples with problems, 5 neighbors or family as informants who knew about the husband and wife and 3 informants as problem solvers. In collecting data using observation techniques, in-depth interviews and documentation. Therefore, the researcher concludes that the causes of domestic violence are economic difficulties, disobedience, bad behavior and jealousy. The methods used to resolve domestic violence are resolved through religious courts and outside areligious courts. The aim is to find out the causes, the approach to the results, the results of the research. It is recommended that prospective brides or future spouses receive technical assistance from the religious office. Keywords: Domestic Violence, Causes, Resolution, Mediators